Adapt to survive: A dynamic capabilities theory approach on Philippine firm adaptability during the COVID-19 pandemic - De Vera, Margarita Cricia Mei D. (Animo Repository, 2021)
The COVID-19 pandemic causes economic shocks, which leads to an increase in the unpredictability of market conditions. In past economic crises, we have witnessed fluctuations in public demand eventually leading to an economic downturn usually met with unfavorable outcomes for private entities. By measuring firm liquidity during a cash crunch, De Vito & Gomez (2020) estimated which firms are more geared for survival during the COVID-19 pandemic. This study aims to do a similar analysis but layering on with the Philippines' dynamic aspects of firm survival. Across sectors within the country, firms face uncertainty brought about by the pandemic. It is imperative to know how these firms in their respective sectors can react to pandemic effects and how firm dynamic characteristics play a pivotal role in the survival of these firms. Using the Dynamic Capabilities Theory (DCT), this study aims to provide a snapshot of managerial insight into the extent to which heightened uncertainty during the pandemic affects firms, given their respective sector-specific nature and market environments. First, this study aims to estimate adaptability through measuring resource base elasticity with respect to changes in sales. Second, it aims to further examine firm reactivity and survival by estimating liquidity ratios using the estimations on resource base elasticity. Lastly, it wants to emphasize the pre dynamics in firm capability, by estimating effects of managerial perception, market conditions, and firm competitiveness on resource base elasticity, through a mixed hierarchical model. Using the DCT framework, this study found that at the resource based level, Philippine firms are equipped with capabilities geared for firm survival during the COVID-19 pandemic and that dynamic aspects are present within firm resource capabilities.